Magnetisation-prepared rapid gradient-echo versus inversion recovery turbo spin-echo T1-weighted images for segmentation of deep grey matter structures at 3 T. Issue 12 (December 2016) - Brandão, S.; Bastos-Leite, A.J.
Highlights: IR–TSE serves as a better source of T1-WI than 3D MPRAGE to segment the striatum and thalamus. None of the structures could be entirely represented by using a standard segmentation algorithm. Binary masks obtained after segmentation of GM on IR TSE T1-WI were found to be more accurate to represent the posterior part of the striatum and the lateral part of the thalamus.